Enhanced stiffness weakening and confinement improvement by the linear electromagnetic effect in relatively high-q and low magnetic-shear plasmas. (10th April 2019) - Kim, J.Y.; Han, H.S.
Abstract: The linear electromagnetic stabilizing effect on the toroidal ion temperature gradient (ITG) mode is usually believed to be weak when plasma beta is low. It is shown that this effect can be significant even in such a plasma if the safety-factor ( q ) profile is in the regime with relatively high q and low magnetic-shear values. Furthermore, this effect is found to induce the profile stiffness weakening by reducing the ITG growth rate slope. These results imply that the linear electromagnetic effect can be an important player for the strong confinement improvement or stiffness weakening observed in negative or optimized shear mode, which typically starts to occur from low beta plasmas.